Early molecular oxidative stress biomarkers of ischemic penumbra in acute stroke. (24th September 2019) - Lorenzano, Svetlana; Rost, Natalia S.; Khan, Muhib; Li, Hua; Batista, Leonardo M.; Chutinet, Aurauma; Green, Rebecca E.; Thankachan, Tijy K.; Thornell, Brenda; Muzikansky, Alona; Arai, Ken; Som, Angel T.; et al.
Abstract : Objectives: To assess whether plasma biomarkers of oxidative stress predict diffusion-perfusion mismatch in patients with acute ischemic stroke (AIS). Methods: We measured plasma levels of oxidative stress biomarkers such as F2-isoprostanes (F2-isoPs), total and perchloric acid Oxygen Radical Absorbance Capacity (ORACTOT and ORACPCA ), urinary levels of 8-oxo-7, 8-dihydro-2′-deoxyguoanosine, and inflammatory and tissue-damage biomarkers (high-sensitivity C-reactive protein, matrix metalloproteinase-2 and -9) in a prospective study of patients with AIS presenting within 9 hours of symptom onset. Diffusion-weighted (DWI) and perfusion-weighted (PWI) MRI sequences were analyzed with a semiautomated volumetric method. Mismatch was defined as baseline mean transit time volume minus DWI volume. A percent mismatch cutoff of >20% was considered clinically significant. A stricter definition of mismatch was also used. Mismatch salvage was the region free of overlap by final infarction. Results: Mismatch >20% was present in 153 of 216 (70.8%) patients (mean [±SD] age 69.2 ± 14.3 years, 41.2% women). Patients with mismatch >20% were more likely to have higher baseline plasma levels of ORACPCA ( p = 0.020) and F2-isoPs ( p = 0.145). Multivariate binary logistic regression demonstrated that lnF2-isoP (odds ratio [OR] 2.44, 95% confidence interval [CI] 1.19–4.98, p = 0.014) and lnORACPCA (OR 4.18, 95% CI 1.41–12.41, p = 0.010) were independent predictors of >20% PWI-DWI mismatch and the stricter mismatch definition, respectively. lnORACTOT significantly predicted mismatch salvage volume (>20% mismatch p = 0.010, stricter mismatch definition p = 0.003). Conclusions: Elevated hyperacute plasma levels of F2-isoP and ORAC are associated with radiographic evidence of mismatch and mismatch salvage in patients with AIS. If validated, these findings may add to our understanding of the role of oxidative stress in cerebral tissue fate during acute ischemia.